analysis of causal conditions of elderly sports development in Iraq - Khshala, Oday Khudhair; Tabesh, Saeid; Dousti, Morteza; Farzan, Farzam; Ashouri, Taghi (مجلة دراسات وبحوث التربية الرياضية, 2025)
This research aims to identify the causal conditions influencing the development of sports for the elderly in Iraq, The study is qualitative in nature and aims to be applied and developmental. The participants in the research included 19 experts and professionals in the field of sports for the elderly in Iraq, who were selected through purposive sampling using a snowball method for interviews ,The qualitative results were categorized into three main categories (selective codes), 12 axial codes, and 37 open codes within the framework of causal conditions ,The findings underscore the need for comprehensive strategies that address these health problems, motivational barriers, and policy deficiencies to promote and enhance sports participation among the elderly.